The Role of Local Communities in Overcoming River Pollution in Peliatan Village - Pradnyani, Ida Ayu Eka; Sueca, Ngakan Putu; Prajnawrdhi, Tri Anggraini (Universitas Ibn Khaldun Bogor, 2024)
Environmental pollution is a common problem that often affects an area. One of them is river pollution. River pollution also occurred in Peliatan Village. The condition of one of the rivers, namely the Mas River, was once used as a landfill or TPA. The role of the community in helping to overcome pollution problems is an initial step that can become a foundation in overcoming river pollution problems in Peliatan Village. In Bali, the existence of community groups is still closely felt, especially in overcoming and finding a problem. Local community groups have a major role in providing aspirations for the progress of their own region. The theory of community empowerment and community based development is the theoretical basis for implementing this research activity. The quality of the riverside space is measured from the indicators of the quality of the waterfront space according to Sutrisno (1997) and is presented descriptively. Research using qualitative methods with case studies and using observation and interview techniques. This method is used to be able to understand and discover phenomena in the field in depth. The results of the study showed that the condition of the river before handling river pollution was that its banks were filled with garbage and made into a landfill. The condition of the river afterwards is that the river becomes clean, orderly and made more attractive with the addition of wall carvings and sculptures. The reappearance of the bad debt tradition and visits from outside the area to Peliatan Village. The role of the community as the dominant role and in collaboration with the Service Village and Traditional Village. Contributions from local communities both in terms of ideas, ideas and material as an important capital in overcoming problems in their own area. This capital will be very useful for development in villages or cities.